The diary of a nobody - Grossmith, George; Grossmith, Weedon (London : Everyman, 2009)
"A hilarious account of suburban life in turn-of-the-century London On moving to the Laurels, Brickfield Terrace, Holloway, Mr Pooter, a clerk in the City, resolves to keep a diary. The result is a faithful record of everyday life, from Mr Pooter's unsuccessful dealings with tradesmen, servants and errand boys to his relationship with his dear wife Carrie and their rakish son Lupin, who has an eye for dubious chorus girls. Details of friends and visitors, meals, high days and holidays, fashion, amusements, jokes, party games, joys and disappointments evoke vividly a vanished way of life. Written with an unselfconscious dignity that is both touching and irresistibly funny, Mr Pooter's diary is a comic masterpiece and a rare piece of social history."
Keywords: Diary